1990
DOI: 10.1111/j.1558-5646.1990.tb05207.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Significance of the Loss of the Chloroplast‐dna Inverted Repeat in the Leguminosae Subfamily Papilionoideae

Abstract: Abstract.-The distribution of a rare chloroplast-DNA structural mutation, the loss of a large inverted repeat, has been determined for 95 species representing 77 genera and 25 of the 31 tribes in the legume subfamily Papilionoideae. This mutation, which is regarded as a derived feature of singular origin within the subfamily, marks a group comprising six temperate tribes, the Galegeae, Hedysareae, Carmichaelieae, Vicieae, Cicereae, and Trifolieae, an assemblage traditionally considered to be monophyletic. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(47 citation statements)
references
References 19 publications
(26 reference statements)
2
45
0
Order By: Relevance
“…Nevertheless, the plastid DNA of the inverted repeat lacking clade (IRLC; see Figs 1, 2; also as in Lavin et al 1990; Wojciechowski et al 2000) in Leguminosae was reported to be inherited paternally or biparentally (Zhang et al 2003), confirmed by cytoplasmic and phylogenetic studies focusing on Medicago L. (paternal transmission; Schumann and Hancock 1989; Masoud et al 1990; Havananda et al 2010) and Wisteria Nutt. (Hu et al 2005; Trusty et al 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, the plastid DNA of the inverted repeat lacking clade (IRLC; see Figs 1, 2; also as in Lavin et al 1990; Wojciechowski et al 2000) in Leguminosae was reported to be inherited paternally or biparentally (Zhang et al 2003), confirmed by cytoplasmic and phylogenetic studies focusing on Medicago L. (paternal transmission; Schumann and Hancock 1989; Masoud et al 1990; Havananda et al 2010) and Wisteria Nutt. (Hu et al 2005; Trusty et al 2007).…”
Section: Discussionmentioning
confidence: 93%
“…5 Furthermore, the M. truncatula plastid genome lacks the large inverted repeat (IR) encoding the plastid ribosomal RNA operon; therefore, the species belongs to the inverted repeat-lacking clade (IRLC) of the Papillionideae subfamily. 6,7 The analyses of chloroplast genes of IR-containing and IRLC plastid genomes revealed that the synonymous substitution rate in IR genes is 2.3-fold lower than in the single-copy genes, whereas uniform substitution rates were found in genomes lacking an IR. 8 A study of IRLC legume species revealed that the ycf4 gene in Lathyrus has at least 20 times higher local point mutation rate than genes elsewhere on the plastid genome and the ycf4-psaI-accD-rps16 region is frequently associated with a gene loss in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that several kinds of inversions interrupted the gene order of the plastome [5-11]. They are generally associated with specific lineages and thus could be a sign of important events in evolutionary diversification [12,13]. …”
Section: Introductionmentioning
confidence: 99%